Some New Solutions of Non Linear Evolution Equations With Mutable Coefficients - Virdi, Jasvinder Singh (Frontiers in Applied Mathematics and Statistics, 2021)
We construct the traveling wave solutions of some NonLinear Evolution Equations (NLEEs) with mutable coefficients arising in different branches of physics and mathematics. we apply a novel ( G'/G )- formalism to construct more general solitary traveling wave solutions of NLEEs such as Sharma- Tasso-Olver with mutable coefficients and Zakharov Kuznetsov equation. Interesting solutions of NLEEs are investigated by traveling wave solutions which are in form of trigonometric, rational, and hyperbolic functions. This may build more unified new solutions for different kinds of such NLEEs with mutable coefficients arising in mathematics and physics. Wolfram Mathematica 11 is used to perform the computation work and their corresponding plots and counter graphs are plotted. This method is found to be more useful and efficient for searching for the exact solutions of NLEEs.